What drives European spinoff value effects? Impact of corporate governance, information asymmetry, and investor irrationality on firm values - Qian, Binsheng (Cranfield University, 2006)
The thesis explores the magnitude and determinants of spinoff value effects using robust methodologies and different theoretical perspectives. From a sample of 170 European spinoffs in the period 1987-2005, I find that spinoff announcement returns are significantly positive while the long-run shareholder value performance of postspinoff firms is insignificant when the cross-sectional return dependence problem is controlled. This is consistent with market efficiency overall in relation to spinoffs. However, this overall efficiency may conceal irrational investor behaviour towards certain types of spinoffs. Assuming investor irrationality, I examine whether investor sentiment affects spinoff wealth effects and spinoff decisions. I use four different proxies to measure investor demand for corporate focus and glamour stocks, and observe a positive association between these proxies and spinoff announcement returns. In addition, I find that offspring, born of spinoffs to cater to investor demand for glamour stocks, significantly underperform various benchmarks including the performance of less glamourous offspring. An improvement in operating efficiency of post-spinoff firms may not be realised if post-spinoff firms have weak corporate governance and agency conflicts are not mitigated. I investigate this issue by examining changes of corporate governance mechanisms around spinoffs. I observe that spinoff firms with a controlling family shareholder have higher announcement stock returns but lower post-spinoff performance than others. Moreover, controlling family shareholders generally reduce their stock ownership in post-spinoff firms, indicating that they may undertake spinoffs to reshuffle their wealth portfolios. I also find that board monitoring and takeover threats for post-spinoff firms positively affect the long-run performance of post-spinoff firms. This thesis further inspects the relationship between information asymmetry between the pre-spinoff parent and the stock market, and spinoff value effects. By employing four different information asymmetry proxies, I find no evidence that a spinoff resolves information asymmetry problems. In contrast, I document some evidence that the information asymmetry problem may be exacerbated following spinoffs when the liquidity of post-spinoff firms is decreased. Taken together, my findings suggest that managers and shareholders should assess the desirability of a spinoff more carefully and take investor irrationality into account. This is the first study that focuses on European spinoffs over a long period and tests various theories concerning the sources of value. It also provides the first time empirical evidence on the validity of the catering theory in the context of spinoffs.